Psychometric Validation of the Indonesian Adolescent Adaptation of the Psychological Inventory of Criminal Thinking Styles - Lucy Lidiawati Santioso; Wisnu Wiradhany; Clara R. P. Ajisuksmo (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This study addresses the need for culturally valid instruments to assess criminal thinking among adolescents in non-Western contexts. Existing measures, such as the Psychological Inventory of Criminal Thinking Styles (PICTS), have limited applicability for adolescent and cross-cultural populations. This study aimed to adapt PICTS into an adolescent-oriented Indonesian version and evaluate its psychometric properties among Indonesian adolescents. A cross-sectional design was used with 550 adolescents aged 14–18 years recruited from educational and correctional settings. The sample was randomly divided for exploratory factor analysis (EFA; n = 275) and confirmatory factor analysis (CFA; n = 275). Reliability was assessed using Cronbach’s alpha and composite reliability, while validity was evaluated using average variance extracted (AVE), heterotrait–monotrait ratio (HTMT), and correlations with APSD-Y. Results supported a four-factor structure consisting of moral disengagement, executive dysfunction, rationalization, and reflective awareness. The final 29-item model showed acceptable fit (CFI = .910, TLI = .901, RMSEA = .039, SRMR = .060), with reliability coefficients ranging from .646 to .858. Concurrent validity was supported by a moderate correlation with APSD-Y scores (r = .441, p < .001). These findings provide preliminary evidence that the Indonesian adolescent adaptation of PICTS is a culturally relevant instrument for assessing criminal thinking among Indonesian adolescents.Penelitian ini dilakukan untuk menjawab kebutuhan akan instrumen yang valid secara budaya dalam mengukur pemikiran criminal (criminal thinking) pada remaja di konteks non-Barat. Instrumen yang tersedia, seperti Psychological Inventory of Criminal Thinking Styles (PICTS), masih memiliki keterbatasan ketika digunakan pada populasi remaja dan lintas budaya. Oleh karena itu, penelitian ini bertujuan mengadaptasi PICTS ke dalam versi yang sesuai untuk remaja Indonesia serta mengevaluasi karakteristik psikometriknya. Penelitian menggunakan desain potong lintang (cross-sectional) dengan melibatkan 550 remaja berusia 14–18 tahun yang direkrut dari lingkungan pendidikan dan pemasyarakatan. Sampel dibagi secara acak untuk analisis faktor eksploratori (EFA; n = 275) dan analisis faktor konfirmatori (CFA; n = 275). Reliabilitas dievaluasi menggunakan koefisien alfa Cronbach dan composite reliability, sedangkan validitas dievaluasi melalui average variance extracted (AVE), heterotrait–monotrait ratio (HTMT), dan korelasi dengan APSD-Y. Hasil penelitian mendukung struktur empat faktor yang terdiri atas moral disengagement, executive dysfunction, rationalization, dan reflective awareness. Model akhir yang terdiri dari 29 aitem menunjukkan kesesuaian model yang memadai (CFI = .910, TLI = .901, RMSEA = .039, SRMR = .060), dengan koefisien reliabilitas berkisar antara .646 hingga .858. Validitas konkuren didukung oleh korelasi positif sedang dengan skor APSD-Y (r = .441, p < .001). Temuan ini memberikan dukungan awal terhadap adaptasi PICTS untuk remaja Indonesia sebagai instrumen yang relevan secara budaya untuk mengukur criminal thinking pada remaja Indonesia.